Алгоритм синтезу експертної системи управління рухом електрорухомого складу на основі рішення рівняння Гамільтона-Якобі-Беллмана - Петренко, Олександр Миколайович; Любарський, Борис Григорович; Глєбова, Марина Леонідівна (НТУ "ХПІ", 2016)
У даній роботі розроблено алгоритм рішення рівняння Гамільтона-Якобі-Беллмана для задачі руху електрорухомого складу на ділянці шляху із заданим профілем і графіком руху, що дозволяє створити експертну систему управління рухом. Особливостями цього алгоритму є застосування штрафних функцій для опису обмежень, що накладаються графіком руху: досягнення потягом кінцевого пункту за заданий час руху, обмеження швидкості на ділянках шляху.

To solve the problem of optimal motion an expert system of conducting an electric rolling stock on a track section is created. The system allows to determine the best modes of the variation of the rolling stock motion on the basis of the criterion of energy consumption for a given average speed. An optimal average speed is selected based on the expert systems of reference vehicle on a section of the route at different average speeds and an integrated efficiency criterion. In this paper, an algorithm for solving the Hamilton-Jacobi-Bellman equation for the problem of motion of an electric rolling stock on a track section with a given profile and motion graphics is developed, which allows to create an expert traffic control system. The feature of this algorithm is the use of penalty functions to describe the restrictions imposed by the timetable, namely, the predetermined time for reaching the destination point by the train, the speed limit on the road sections, as well as the lack of downtime during the train motion. A unified penalty function approach is also used for imposing restrictions on the clutch. This approach allows to reduce significantly the computing time and standardize (simplify) the energy cost calculations.
An algorithm for synthesizing an expert electric rolling stock traffic control system on the basis of solution of the Hamilton-Jacobi-Bellman equation
Keywords: штрафні функції; опір руху; ЕРС; штрафні функції; penalty function; movement resistance